PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE PEER LESSON DISERTAI KUIS TERHADAPPEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 1 LENGAYANG TAHUN PELAJARAN 2012/2013 KAB. PESISIR SELATAN - Putra, Jelfio Drahsas; Anggraini, Vilia; Febriana, Rina (Pendidikan Matematika, 2013)
The background of this research is because the low understanding in mathematics of VII grade students and caused by a centered-teacher learning. The purpose of this research is to find which one is better between the using in srategy active learning type Peer Lesson whit quis compared with conventional learning Â studentâs understanding of learning mathematics in SMPN 1 Lengayang. This is the kind of experiment research, with the subject random. The population of this research is all of VII grade students SMPN 1 Lengayang. The sample is taken randomly and VII.2 as a experiment class and VII.4 as a control class. The instrument of this research is the find test with indicator consept understanding mathematics. The form of test is a essay concept with reliable test is 0,844. The analysis data used is the test of t with MINITAB software. Based of result in analysis data found that two sample classes are distributed normally and having the homogeny variation in Â = 0,05. The hypothesis testing find P-value 0,004 and itâs smaller than at . So, itâs can concluded that the studentâs mathematics concepts understanding by using srategy active learning type Peer Lesson whit quis is better than the conventional learning in VII grade students of SMPN 1 Lengayang in a level 95%.